ANALYSIS OF KNOWLEDGE LEVEL AND LONELINESS OF THE ELDERLY IN PENIWEN VILLAGE, MALANG REGENCY - Eric Dino Tandoyo; Minarni Wartiningsih; Valeria Rosalind Angkawidjaja; Bella Ayu Adinda; Adam Hilman Wibisono; Marilyn Firmantho; Erfince Wanimboe; Thomy Aljabbari Zaman (Jurnal Endurance, 2023)
The elderly is someone more than or equal to 55 years old with a process of physical, biological, cognitive, psychological, economic, and social role changes in society. The main psychological problem in the elderly is loneliness, feelings of isolation because they feel different from other people's circumstances. The purpose of the study was to determine the level of loneliness and the level of knowledge about loneliness in the elderly in Peniwen Village. This type of research is quasi-experimental with a one-group pretest-posttest design. The research sample amounted to 30 people with the sampling technique, namely the total sampling system. The research instrument used the De Jong Giervield Loneliness questionnaire and a pretest-posttest related to knowledge about loneliness. Based on the results of the questionnaire, 29 (96.67%) respondents experienced moderate loneliness and 1 (3.33%) respondent experienced severe loneliness. In the pre-test results, there were no respondents who answered 10 post-test numbers correctly. After being given counseling, there was an increase in value as shown by 20 (66.70%) respondents answering 10 post-test numbers correctly. Based on the Wilcoxon test, a significance level value of p=0.000 or <0.05 was obtained, which means that there is a difference between the knowledge of respondents before counseling and after counseling about loneliness. The conclusion is that most of the elderly of Peniwen village experience moderate levels of loneliness and there are differences in knowledge before and after counseling about loneliness in the elderly.